STUDY OF TEMPERATURE EFFECT ON THE HARDNESS FOR EPOXY RESIN AND UNSATURATED POLYESTER - Baghdad Science Journal (مجلة بغداد للعلوم)
This search aim to measure Hardness for Epoxy resin and for unsaturated Polyester resin as base materials for composite Hybrid and the materials used is Hybrid fiber Carbon-Kevlar. The Hand Lay-up method was used to manufacture plates of Epoxy resin (EP) and unsaturated Polyester EP,UPE backed by Hybrid fiber (Carbon-Kevlar) and with small volume fraction 5,10 and 15 for every there are Layer of fibers (1,2 and 3). The hardness test was count for material EP, UPE resin and there composites and that we notice that the Hardness (HB) decreased with increase of temperatures.